PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED TEACHING TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 38 SIJUNJUNG - Melpi Mutiara, Ega; Cesaria, Anna; Suryani, Mulia (Pendidikan Matematika, 2014)
ABSTRACTThis research based on lowest of students understanding of mathematical concept, the fear of them to give their opinion orÂ  answer the teacherâs questions. Also, students do not active in learning process in class VIII SMPN 38 Sijunjung. The purpose of this research is to know studentâs understanding of mathematical concept by using learning active guided teaching is better than using convensional strategy at students class VIII SMPN 38 Sijunjung. Kind of this research is experiment by using random research about subject instrument used in thisÂ  with research is test understanding of mathematical concept concept. Kind of the test is essay reliabilitas of test 0,7. Based on result of data analized knowed that sample class are normal and homegenous. The result of hyphotesis test is p-value is smaller than Î±, so the hyphotesis is acceptance.it was that the mathematical conceptual understanding of the students taught by using learning active strategy guided teaching is better than using convensional Â learning.Â